Influence of seed size and ecological factors on the germination and emergence of field bindweed (Convolvulus arvensis) - Tanveer,A (2013)
An understanding of seed germination ecology of weeds can assist in predicting their potential distribution and developing effective management strategies. Influence of environmental factors and seed size on germination and seedling emergence of Convolvulus arvensis (field bindweed) was studied in laboratory and greenhouse conditions. Germination occurred over a wide range of constant temperatures, between 15 and 40 ºC, with optimum germination between 20 and 25 ºC. Time to start germination, time to 50% germination and mean germination time increased while germination percentage and germination index decreased with an increase in temperature from 20 ºC, salinity and osmotic stress. However, germination was tolerant to low salt (25 mM) or osmotic stress (0.2 MPa), but as salinity and osmotic stress increased, germination percentage and germination index decreased. Seeds of C. arvensis placed at soil surface showed maximum emergence and decreased as seeding depth increased. Seeds of C. arvensis germinated over a wide range of pH (4 to 9) but optimum germination occurred at pH 6 to 8. Under highly alkaline and acidic pH, time to start germination, time to 50% germination and mean germination time increased while germination percentage and germination index decreased. Increase in field capacity caused decreased time to start germination, time to 50% germination and mean germination time but increased germination percentage and germination index. Bigger seeds had low time to start germination, time to 50% germination and mean germination time but high germination percentage and germination index. Smaller seeds were more sensitive to environmental factors as compared to larger or medium seeds. It can be concluded that except for pH, all environmental factors and seed sizes adversely affect C. arvensis as regards seed germination or emergence and germination or emergence traits, and larger seeds result in improved stand establishment and faster germination than small seeds, regardless of moisture stress or deeper seeding depth.